Skin in the Game and Moral Hazard - CHEMLA, GILLES; HENNESSY, CHRISTOPHER A. (Journal of Finance, 2014)
ABSTRACT What determines securitization levels, and should they be regulated? To address these questions we develop a model where originators can exert unobservable effort to increase expected asset quality, subsequently having private information regarding quality when selling ABS to rational investors. Absent regulation, originators may signal positive information via junior retentions or commonly adopt low retentions if funding value and price informativeness are high. Effort incentives are below first‐best absent regulation. Optimal regulation promoting originator effort entails a menu of junior retentions or one junior retention with size decreasing in price informativeness. Zero retentions and opacity are optimal among regulations inducing zero effort.